2019
DOI: 10.1029/2019gl085175
|View full text |Cite
|
Sign up to set email alerts
|

Gravity‐Induced Bubble Ripening in Porous Media and Its Impact on Capillary Trapping Stability

Abstract: Capillary or residual trapping is considered one of the safest geologic CO 2 storage mechanisms due to its hydrodynamic stability. We present a first study of the impact of gravity on Ostwald ripening in porous media and show it may render capillary trapping thermodynamically unstable. Gravity induces a vertical chemical potential gradient that leads to the upwards diffusion of CO 2 . Thus, bubbles at shallower depths grow at the expense of bubbles in deeper strata, leading to the formation of an overriding ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Garing et al (25) experimentally measured the equilibrium capillary pressure of trapped air bubbles inside sandstone and bead-pack samples. They found that, unlike bubbles within a bulk fluid, the P c of trapped bubbles shows no clear dependence on V and seems to fall within a bounded interval, except for vanishingly small V. Xu et al (40) proposed an empirical correlation for the P c trapped bubbles based on microfluidic observations. In this correlation, as V increases, P c decreases until a minimum is reached and then increases linearly.…”
mentioning
confidence: 99%
“…Garing et al (25) experimentally measured the equilibrium capillary pressure of trapped air bubbles inside sandstone and bead-pack samples. They found that, unlike bubbles within a bulk fluid, the P c of trapped bubbles shows no clear dependence on V and seems to fall within a bounded interval, except for vanishingly small V. Xu et al (40) proposed an empirical correlation for the P c trapped bubbles based on microfluidic observations. In this correlation, as V increases, P c decreases until a minimum is reached and then increases linearly.…”
mentioning
confidence: 99%
“…questions about basis for the extrapolation to "field rates" for estimating critical gas saturation. It is possible that at field scale large column height can lead gravity-induced ripening [51] creating possible connected paths and associated mobility. The growth kinetics, however, is diffusion limited which is expected to occur on a time scale of years at relevant length scales [51].…”
Section: Discussionmentioning
confidence: 99%
“…Even though diffusion is only impacted in the percent range by the geometric constraint of the pore space, the increase in curvature and the associated (capillary) pressure for growth past a pore throat causes a de-facto anti-ripening effect with pore throats acting as barriers for growth [49] which can only be overcome by a significant driving forces, e.g. significant gravity potential over large column height [51]. Ultimately, both phenomena of ripening and anti-ripening are the result of the same underlying physical process of coarsening in porous media.…”
Section: Pore Scale Fluid Configuration In the 2-component Systemmentioning
confidence: 99%
“…The selected simulation parameters are listed in Table S1 in Supporting Information . The liquid and gas phases are brine and scCO 2 , and some parameters are obtained from the literature(Busch & Amann‐Hildenbrand, 2013; Liu et al., 2012; Xu et al., 2019).…”
Section: Numerical Analysismentioning
confidence: 99%
“…A study using an isothermal gravity/chemical equilibrium model found that the composition of oil and gas mixtures stored in deep strata changed significantly with the depth, and gravity affected the chemical potential of the phase, resulting in the redistribution of the gas‐liquid composition in the vertical direction (Wheaton, 1991; Whitson & Belery, 1994). A gravity‐induced ripening bubble model was proposed for the first time to investigate the temporal variation of the bubbles in different pore structures during ripening in the mass transfer process (Xu et al., 2019). The theoretical mass transfer time obtained by this theoretical model is relatively long, and gravity can affect the process by altering the magnitude and direction of chemical potential gradients.…”
Section: Introductionmentioning
confidence: 99%